Laying performance of 5th generation of BLRI improved native duck (Bangladesh Journal of Livestock Research, 2021)
This research was aimed to improve the egg production performances and to estimate the selection response of fifth generation (G5) of deshi white (Rupali) and white breasted black (Nageswari) duck genotypes through an individual selection program. All the ducks were reared in an open sided duck house. Diet containing 17.5% CP and 2750 Kcal ME/kg and fresh water provided twice daily in the morning and evening. Individual egg production was recorded from each duck. After 40 weeks of age, female ducks were selected on the basis of selection index and selection differences, selection intensity and responses were also measured. Egg weight, egg production and feed intake were recorded and FCR, egg mass was calculated. All recorded data were analyzed by SAS and differences were determined by DMRT. The selection criteria of fifth generation (G5) of both duck genotypes were studied. As a result of selection, age at sexual maturity (day), egg weight (g) and egg production % were expected to improve by -1.63d, 0.60g, 1.01% and -0.85day, 0.39g, 0.47% for Rupali and Nageswari ducks, respectively. Egg mass was significantly (p